CALIBRATION OF INFRASOUND SENSORS: AN EXTENSIVE STUDY ON ENHANCING DIFFERENTIAL NOISE SUPPRESSION - Thompson, David (Ayden International Journal of Basic and Applied Sciences, 2024)
Infrasound, characterized by its low frequency, long wavelength, and extensive propagation range, is a pervasive phenomenon resulting from natural events and human activities. Its ability to penetrate over long distances with minimal attenuation renders it invaluable in applications ranging from environmental monitoring to military surveillance. Infrasound's role in detecting nuclear explosions, monitoring supersonic aircraft, and tracking large weapons targeting underscores its significance in national defense. The propagation of infrasound remains unhindered by visibility or electromagnetic interference, making it an exceptional monitoring tool, ideal for long-range surveillance. The field of infrasound research has witnessed rapid expansion, leading to the growth of the infrasound industry. As a consequence, the accuracy of infrasound sensors and calibration capabilities has become a focal point for improvement. This endeavor seeks to advance infrasound research and enhance the analytical capabilities of infrasound signal data. Key to the precise measurement of infrasound sound pressure is the calibration of infrasound sensors, which serves as the linchpin for accurate monitoring and analysis in a multitude of domains.